2016
DOI: 10.1126/scisignal.aaf3739
|View full text |Cite
|
Sign up to set email alerts
|

Selective control of up-regulated and down-regulated genes by temporal patterns and doses of insulin

Abstract: Secretion of insulin transiently increases after eating, resulting in a high circulating concentration. Fasting limits insulin secretion, resulting in a low concentration of insulin in the circulation. We analyzed transcriptional responses to different temporal patterns and doses of insulin in the hepatoma FAO cells and identified 13 up-regulated and 16 down-regulated insulin-responsive genes (IRGs). The up-regulated IRGs responded more rapidly than did the down-regulated IRGs to transient stepwise or pulsatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…We have found that insulin selectively regulates not only a signaling pathway but also metabolites and gene expression via its temporal patterns using rat hepatoma Fao cells (Kubota et al, 2012;Noguchi et al, 2013;Sano et al, 2016). Therefore, metabolites and gene expression might also be selectively regulated in vivo.…”
Section: In Vivo Temporal Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that insulin selectively regulates not only a signaling pathway but also metabolites and gene expression via its temporal patterns using rat hepatoma Fao cells (Kubota et al, 2012;Noguchi et al, 2013;Sano et al, 2016). Therefore, metabolites and gene expression might also be selectively regulated in vivo.…”
Section: In Vivo Temporal Codingmentioning
confidence: 99%
“…Among them, metabolic regulation, such as gluconeogenesis, glycogenesis, protein synthesis, and lipid synthesis, is a major target of insulin action and is regulated through the insulin-AKT (also known as protein kinase B [PKB]) signaling pathway and gene regulation in vivo (Whiteman et al, 2002;Yugi et al, 2014). Using rat hepatoma Fao cells, we have revealed that insulin selectively regulates the AKT pathway molecules, metabolism, and gene expression, via its temporal patterns (Kubota et al, 2012;Noguchi et al, 2013;Sano et al, 2016). However, as these results came from a cultured cell line, it remains unknown whether selective regulation by insulin exists in the liver or not.…”
Section: Introductionmentioning
confidence: 99%
“…To respond properly to insulin, cells must detect both induced and basal insulin signals and properly interpret each type of insulin signal. We previously showed that signaling proteins, such as Akt ( Kubota et al., 2012 , Kubota et al., 2018 ); metabolites, such as glycogen ( Noguchi et al., 2013 ); and genes, such as glucose-6-phosphatase ( G6Pase ) and phosphoenolpyruvate carboxykinase1 ( Pck1 ) ( Sano et al., 2016 ), show distinct changes in the activity, abundance, or expression in response to a transient high dose or a sustained low dose of insulin. However, the pathways that selectively transmit the induced and basal insulin signals to regulate selective functions have yet to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion method was rapid within a minute (bolus ingestion), and continuous over the course of 2 hours (2 h-continuous ingestion). For continuous ingestion, we connected the tube to noncontact microdispenser robot (Mr. MJ; MECT Corporation) (Sano et al, 2016) and glucose solution was ingested from tube. To equalize the volume of ingested glucose solution, glucose solution, TRELAN-G75 (AJINOMOTO), was diluted with distilled water into a total volume 225 ml.…”
Section: Star⋆methodsmentioning
confidence: 99%